An appraisal of the quality of sandcrete blocks used for construction in Lagos metropolis - Awolusi, I. G.; Soyingbe, A. A.; Oyeyipo, O. O. (Penerbit UKM, 2015)
Sandcrete blocks have been in use in many parts of the world for a very long time. The prominence of sandcrete blocks as part of the local building materials that make up the wall units in a building or any construction work cannot be underestimated because houses are mostly built of blocks. This paper examines the quality of machine-vibrated hollow sandcrete blocks used on construction sites in Lagos metropolis. A total of sixty (60) units of machine-vibrated sandcrete blocks were sampled from ten (10) manufacturers within Lagos Mainland. Three (3) samples of 450mm x 225mm x 225mm blocks and another three (3) of 450mm x 150mm x 225mm blocks were selected from each of the 10 manufacturers to make the total of 60 blocks. Also, a total of forty (40) units of machine-vibrated sandcrete blocks were produced based on the requirements of the NIS 87:2004 standards for sandcrete blocks. The blocks obtained from manufacturers as well as those produced were tested to determine their quality in terms of three parameters which were the compressive strength, density and dimensional tolerance. The results obtained revealed that the compressive strength of the blocks obtained from manufacturers ranged from 0.21N/mm2 to 1.26N/mm2 for 225mm wide blocks and from 0.28N/mm2 to 0.95N/mm2 for 150mm wide blocks which are far below the minimum NIS requirements of 3.45N/mm2 and 2.5N/mm2 respectively. The densities of these blocks were found to be satisfactory with the requirements of the standard while the dimensions were inaccurate in terms of web thicknesses. It was recommended that the regulatory bodies should be empowered to control production processes and implement effective strategies such as mobile testing to ascertain the quality of sandcrete blocks.